2011
DOI: 10.1016/j.applthermaleng.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Expanders for micro-CHP systems with organic Rankine cycle

Abstract: ABSTRACT:The continual increases in global energy demand and greenhouse gas emissions call for more and more utilisation of sustainable energy sources, such as solar energy, biomass energy, and waste heat. Solar thermal energy, the heat of biomass combustion and waste heat may be used to drive a combined heat and power (CHP) system.In recent years, several micro-CHP systems with organic Rankine cycle (ORC) suitable for domestic applications (1-10kW e ) driven by solar thermal, biomass-fired boilers and waste h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(112 citation statements)
references
References 14 publications
0
108
0
2
Order By: Relevance
“…Przegląd różnych typów ekspanderów, głównie o mocy do 10 kWel, rozwijanych obecnie przez ośrodki przemysłowe i naukowe, został zamieszczony np. w pracy [2]. Żaden z omawianych ekspanderów nie jest jeszcze gotowy do produkcji seryjnej i sprzedaży na większą skalę.…”
Section: Wprowadzenieunclassified
“…Przegląd różnych typów ekspanderów, głównie o mocy do 10 kWel, rozwijanych obecnie przez ośrodki przemysłowe i naukowe, został zamieszczony np. w pracy [2]. Żaden z omawianych ekspanderów nie jest jeszcze gotowy do produkcji seryjnej i sprzedaży na większą skalę.…”
Section: Wprowadzenieunclassified
“…Literature reviews on small-scale expanders propose different configurations [86]. The options available present both pros and cons that complicate the selection of a single "ideal" expander.…”
Section: Expander Selectionmentioning
confidence: 99%
“…• Freezing point: The freezing point needs to be well below the minimum ambient temperature in the site in which the system is installed, to avoid solidification of the working fluid during periods of inactivity of the ORC plant [85]. • Cycle top pressure: It is important to keep the cycle top pressure well below the fluid critical pressure [86]. This is necessary to prevent the formation of liquid droplets during the expansion process and to overcome instability during vaporization.…”
Section: R 143amentioning
confidence: 99%
“…Qiu et al [11] evaluated several expansion devices for micro-CHP ORC systems including turbine, scroll, screw and vane expanders, and suggested that both scroll and vane expanders are suitable for micro-scale ORC systems with capacity ranging from 1kW to 10kW. Ali Tarique et al [12] stated that a scroll expander is the best choice for small capacities due to the more flexible operation characteristic.…”
Section: Introductionmentioning
confidence: 99%